Correlations of erythrocytic oligomer α-synuclein levels with age, sex and clinical variables in patients with Parkinson’s disease - Lu, Zhe; Yu, Xiaohan; Li, Pengjie; Wang, Yiming; Deng, Yeyun; Li, Xin; Wang, Chaodong; Yu, Shun (Frontiers in Aging Neuroscience, 2024)
Introduction: Oligomeric alpha-synuclein in red blood cells (RBC-o-α-Syn) has been shown to be increased in patients with Parkinson's disease (PD). However, factors that affect RBC-o-α-Syn levels remain to be elucidated. The aim of this study is to analyze the correlations between RBC-o-α-Syn levels and the age, sex and different clinical variables of patients with PD. Methods: 167 patients with PD and 119 healthy controls (HC) were enrolled in this study. The patients with PD were diagnosed based on the MDS clinical diagnostic criteria for PD. All participants were evaluated for their clinical characteristics. Western blot analysis was used to examine the molecular sizes of RBC-o-α-Syn. A newly established chemiluminescent immunoassay was used to measure RBC-o-α-Syn levels.Results: Higher RBC-o-α-Syn levels were detected in PD patients than in HC subjects. The receiver operating characteristic (ROC) curve indicated that a cut off value of 55.29 ng/mg discriminated well between PD patients and HC subjects, with a sensitivity of 67.66% (95% CI: 60.24-74.29%), a specificity of 88.24% (95% CI: 81.22-92.86%), and an area under the curve (AUC) of 0.857. The levels of RBC-o-α-Syn were higher in female than male patients (p = 0.033). For different subtypes, the levels of RBC-o-α-Syn were higher in the MIX subtype than the tremor-dominant (TD) PD. In addition, the levels of RBC-o-α-Syn were higher in patients with than without cognitive impairment (p = 0.016), and negatively correlated with Mini-Mental State Examination (MMSE) scores (r = -0.156, p = 0.044). R 2 删除[LUZHE [2]]: